Supply chain innovation for competing in highly dynamic markets : challenges and solutions - Evangelista, Pietro, 1963- (Hershey, PA : Business Science Reference, 2012)
'This book investigates the role of innovation in the management of supply chains of today, focusing on supply chain integration from both strategic and operational perspectives and the impact of information technology-related innovation in supply chain and logistics service industries'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business logistics; Business logistics -- Information technology; Business logistics -- Technological innovations